2022
DOI: 10.2196/27388
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mobile Health Platforms for Depression and Anxiety: Content Analysis Through a Systematic Review of the Literature and Systematic Search of Two App Stores

Abstract: Background Mobile health (mHealth) platforms show promise in the management of mental health conditions such as anxiety and depression. This has resulted in an abundance of mHealth platforms available for research or commercial use. Objective The objective of this review is to characterize the current state of mHealth platforms designed for anxiety or depression that are available for research, commercial use, or both. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 190 publications
1
14
0
Order By: Relevance
“…In addition, as the level of scientific evidence is difficult to assess, mental health professionals chose "N/A The application has not been tested" in most cases to answer item 19, which therefore could not be included in the statistical analysis. To our knowledge, of the 12 apps, only 1 (8%) app included in this study (Sanvello) was indexed in PubMed [45][46][47][48]. Myers et al [45] evaluated apps for depression self-management, Mehdi et al [46] evaluated apps for Tinnitus, and Lau et al [47] evaluated apps for mental health.…”
Section: Principal Findingsmentioning
confidence: 99%
“…In addition, as the level of scientific evidence is difficult to assess, mental health professionals chose "N/A The application has not been tested" in most cases to answer item 19, which therefore could not be included in the statistical analysis. To our knowledge, of the 12 apps, only 1 (8%) app included in this study (Sanvello) was indexed in PubMed [45][46][47][48]. Myers et al [45] evaluated apps for depression self-management, Mehdi et al [46] evaluated apps for Tinnitus, and Lau et al [47] evaluated apps for mental health.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Importantly, our research of the literature was quite broad, including correlational studies in addition to experimental studies and clinical trials. A recent review of mobile apps for depression and anxiety identified 179 apps available to consumers, but only three apps-less than 2%-had evidence from both RCTs and real-world effectiveness (RWE) trials (Leong et al, 2022). Yet, more than 20% of the apps appeared under the category of medical apps on the app stores (Leong et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…A recent review of mobile apps for depression and anxiety identified 179 apps available to consumers, but only three apps-less than 2%-had evidence from both RCTs and real-world effectiveness (RWE) trials (Leong et al, 2022). Yet, more than 20% of the apps appeared under the category of medical apps on the app stores (Leong et al, 2022). Notably, apps that are categorized as 'medical' may be perceived by consumers as being backed by scientific evidence even without making explicit claims of being evidence-based.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Acceset intervention addresses 3 gaps in the current research. First, our published work, undertaken to identify mobile health (mHealth) platforms across popular app stores and academic databases, found 302 anxiety and depression mHealth platforms that are currently available [ 36 ]. Of note, most mHealth platforms on the market are not designed for a specific age group and, even of those used academically, only 13% are designed specifically for emerging adults.…”
Section: Introductionmentioning
confidence: 99%